Dinamika Perubahan Sosial dan Dampaknya Terhadap Pembangunan Berkelanjutkan: Perspektif Multidisiplin - Muhammad Luthfi Naufal; Endang Rahmawati; Salsa Bilkis Kuds; Ivan Darmawan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Social change has a significant impact on sustainable development from a multidisciplinary perspective. These impacts include social and political aspects. In the social aspect, changes in values, norms and social behavior can affect social relations, interaction patterns, as well as family structure, gender roles, migration patterns, education levels and public health. In the political aspect, changes in political order, political participation and power dynamics can affect public policy, institution building, as well as political stability, transparency, accountability and social justice in the context of development. Therefore, a comprehensive understanding of the impact of social change is necessary in designing sustainable development policies and strategies, with the aim of achieving political stability, community empowerment, and the achievement of social justice in the process of sustainable development.